Detection of the amplitude modulation for modulating signals characterised by different crest factors - Rybicka, W.; Sęk, A. (Archives of Acoustics, 2003)
This study is concerned with the detection of amplitude modulation (AM) of a tonal signal for modulating signals characterised by a different crest factor and a low frequency. The purpose was to show that the root-mean-square (RMS) value of the modulating signal is not a sufficient measure of the modulation perceived by listeners. In the first experiment, using the 2AFC method with an adaptation procedure, the AM detection thresholds were determined for a 1-kHz tone modulated with 3-component harmonic complexes, the components of which had the same amplitudes. The starting phases of the complexes were chosen arbitrary to obtain the highest (2.44) and the lowest (1.89) values of the crest factor of the same root-mean-square values. The fundamental frequencies of the modulator were 1, 2 Hz and 4 Hz. The AM thresholds gathered for these modulators were characterized by a certain scatter that makes impossible the drawing of any conclusion concerning the influence of the crest factor on those thresholds. Therefore in the second experiment psychometric functions were determined for the detection of AM using the same carrier and modulators. However, the results of this experiment did not provide unambiguous evidence for a statistically significant effect of the crest factor on the psychometric functions and the AM threshold values. Since the modulators used in the first two experiments were characterised by too small differences in the crest factor, the modulating signal in the third experiment was a harmonic complex consisting of ten pure tones of the same amplitude. The starting phases of all components were chosen so as to obtain signals characterised by the highest (4.47) and the lowest (1.58) crest factor. For these modulating signals, the probability of AM detection was found to depend significantly on the crest factor, i.e. the detection of the AM was considerably easier when a modulating waveform characterised by the highest crest factor was used. The results of this experiment suggested that, at least for the low-frequency modulator, the description of the AM thresholds by means of the RMS values of the modulator is somehow misleading and does not express properly the abilities of the auditory system to detect low-frequency amplitude changes. It has been also suggested that for a modulating signal of a high crest factor the listeners can follow the amplitude changes over time only when the changes are slow enough, i.e. when sidebands produced by the amplitude modulation are not resolved in the auditory periphery.